2018
DOI: 10.17509/ijal.v8i1.11481
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ motivation and competence in an Indonesian context as assessed within the framework of Maslow’s and Herberg’s theories

Abstract: Using regression and descriptive analyses, this research was carried out to measure the nature of teachers’ motivation as indicated by their job commitment and satisfaction, which was then used to predict the EFL teachers’ competence. The participants were 42 high school English teachers from both public and private schools in Binjai, North Sumatera Province. Likert-type inventory on teachers’ motivation, with items focused on job commitment and job satisfaction, and a fact-based, multiple choice assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…This study aligns with a body of research showing that teachers' lack of motivation and interest in teaching has a detrimental impact on students' motivation (Inayatullah & Jehangir, 2012; Bonta, 2019; Ghonsooly et al, 2017;Frenzel et al, 2009;Tambunan et al, 2018). EFL teachers lacking in motivation and passion for their jobs will hinder students' progress because unmotivated teachers make language learning uninteresting.…”
Section: B Behaviour-related Factorssupporting
confidence: 85%
See 1 more Smart Citation
“…This study aligns with a body of research showing that teachers' lack of motivation and interest in teaching has a detrimental impact on students' motivation (Inayatullah & Jehangir, 2012; Bonta, 2019; Ghonsooly et al, 2017;Frenzel et al, 2009;Tambunan et al, 2018). EFL teachers lacking in motivation and passion for their jobs will hinder students' progress because unmotivated teachers make language learning uninteresting.…”
Section: B Behaviour-related Factorssupporting
confidence: 85%
“…Teachers' lack of motivation and interest in teaching has also been highlighted as having a negative impact on students' motivation (Bonta, 2019;Ghonsooly et al, 2017;Frenzel et al, 2009;Tambunan et al, 2018). If EFL teachers lack enthusiasm and passion for their jobs, it affects their students by making language learning appear unappealing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los pocos estudios llevados a cabo en Indonesia se han limitado a profesores de idiomas (e.g., Aritonang, 2014; Tambunan, Hamied, & Sundayana, 2016). Debido a las limitaciones en el diseño de la investigación y a cuestiones relacionadas con la especificidad de la asignatura escolar, estos estudios aportan poco conocimiento sobre la motivación de los profesores indonesios.…”
Section: Relación Entre La Motivación Docente Y El Comportamiento Doc...unclassified
“…The few studies that have been conducted in Indonesia have been limited to language teachers (e.g., Aritonang, 2014; Tambunan, Hamied, & Sundayana, 2016). Due to limitations in research design and issues of school-subject specificity, these studies provide little insight into the motivation of Indonesian teachers.…”
mentioning
confidence: 99%
“…Further, Nawaz and Yasin (2015) write that employees are motivated by handsome prompt salary, unbiased appraisals, positive behavior of students, presence of rooms, friendly environment, availability of learning resources, small class size, less distance from the school, selecting upper class as target market and autonomy given to school teachers. Moreover, Tambunan et al (2018) reported that motivation as indicated by both teachers' commitment and satisfaction could have a significant impact on the competence and in achieving its predetermined goals, committed and satisfied human resources are therefore considered as the most critical assets. Teacher motivation is very critical in achieving academic excellence.…”
Section: Introductionmentioning
confidence: 99%